Water polo: technical and tactical shot indicators between winners and losers according to the final score of the game - Garcia-Marin, P.; Argudo Iturriaga, F. M. (International Journal of Performance Analysis in Sport, 2017)
The objective of this study was to compare the technical and tactical shot indicators in water polo between the winners and losers in balanced (=3 goals difference) and unbalanced (>3 goals) matches in each situational framework (even action, counter-attack, power play and penalty). A total of 2378 shots from the 44 women`s matches in the XV World Championship were analysed. A descriptive analysis and a variance analysis were performed for comparison of means (p = .05). No significant differences were found in the balanced matches. In unbalanced matches, differences arose in even action (zone of origin of prior pass, reception, position, free shot, result and goal zone), counter-attack (position and goalie position in width) and power play (technical gesture, result, goal zone, defender orientation, contact and proximity between defender and attacker). No differences were found in the indicators analysed for penalty. The notational analysis allows for the discrimination of performance factors according to the winner-loser condition and suggests practical applications for training in shooting.